2000
DOI: 10.1002/1096-987x(20010130)22:2<135::aid-jcc1>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Role of the anomeric effect in methanediamines in the gas phase and aqueous solutions

Abstract: An ab initio study of methylenediamine and several methylated derivatives in the gas phase and aqueous solution was performed. The conformational preferences can be considered adequately described at the HF/6-31G * * //HF/6-31G * * level, because these results agree with those obtained using larger basis sets and including ZPE and electron correlation. The energy ordering is clearly dependent on the number and position of the methyl groups present in a molecule. For a first set of the compounds, the energies o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 47 publications
(10 reference statements)
1
9
0
Order By: Relevance
“…Also, similar attenuations of the anomeric effect in the presence of a solvent were reported for structure 2 and related systems such as 2-methoxytetrahydropyran. , The reduction of the energy gap between 1 gg and 1 gg′ is also significant for all the solvents here considered. In contrast, the solvent enlarges the stabilization of the methanediamine conformers with favorable anomeric interactions: 3 tt and 3 tg , as found by Carballeira and Pérez-Juste in aqueous solution at the HF level . The reason why solvents give rise to opposite effects in O−C−O- and N−C−N-containing anomeric compounds is one of the points explained by our present QTAIM analysis (see below).…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Also, similar attenuations of the anomeric effect in the presence of a solvent were reported for structure 2 and related systems such as 2-methoxytetrahydropyran. , The reduction of the energy gap between 1 gg and 1 gg′ is also significant for all the solvents here considered. In contrast, the solvent enlarges the stabilization of the methanediamine conformers with favorable anomeric interactions: 3 tt and 3 tg , as found by Carballeira and Pérez-Juste in aqueous solution at the HF level . The reason why solvents give rise to opposite effects in O−C−O- and N−C−N-containing anomeric compounds is one of the points explained by our present QTAIM analysis (see below).…”
Section: Resultssupporting
confidence: 71%
“…In contrast, the solvent enlarges the stabilization of the methanediamine conformers with favorable anomeric interactions: 3tt and 3tg, as found by Carballeira and P erez-Juste in aqueous solution at the HF level. 30 The reason why solvents give rise to opposite effects in O-C-O-and N-C-N-containing anomeric compounds is one of the points explained by our present QTAIM analysis (see below). Finally, for fluoromethanol, the influence of the solvent is moderate, yielding variations in the relative stability of conformers that are below 1 kcal mol -1 , with regard to the gas phase.…”
Section: ' Computational Detailsmentioning
confidence: 77%
“…However, there are also anomeric systems such as 2-carbomethoxy-1,3-dithiane in which increasing the polarity of the solvent favors axial conformation . With the enormous experimental measurements of the solvent effect on the equilibrium between α and β anomers, computational studies have also been conducted in order to elucidate the forces governing the anomeric effect and reconcile the differential behaviors of different anomeric systems in solution. , Because of the complexity of solvent structures, most works are based on implicit solvent models, notably the polarized continuum model (PCM). For instance, Carballeira and Pérez-Juste probed the conformational preferences of methylenediamine and several methylated derivatives in the gas phase and aqueous solution. , They claimed that the charge delocalization is the main cause for the anomeric effect based on the NBO analysis, and PCM computations showed that the anomeric effect is not reduced but enlarged in water, though the electrostatic interaction is largely responsible for the energetic changes, and depends strongly on local solute–solvent interactions. Vila and co-workers developed an interpretative model based on the quantum theory of atoms in molecules (QTAIM) for the anomeric effect and analyzed a number of anomeric systems in three solvents .…”
Section: Introductionmentioning
confidence: 99%
“…A recent ab initio study of methylated methylendiamines in the gas phase as well as aqueous solution on the HF/6-31G**//HF/6-31G** level showed that less substituted derivatives (e.g., methylenediamine and N -methyl-methylenediamine) adopted conformers related to the presence of an anomeric effect …”
Section: Introductionmentioning
confidence: 99%
“…17 A recent ab initio study of methylated methylendiamines in the gas phase as well as aqueous solution on the HF/6-31G**// HF/6-31G** level showed that less substituted derivatives (e.g., methylenediamine and N-methyl-methylenediamine) adopted conformers related to the presence of an anomeric effect. 18 However, sterically crowded analogues (e.g., N,N,N′,N′-tetramethyl-methylenediamine) adopted a reverse orientation, indicating that the origin for a reverse anomeric effect is due to steric crowding.…”
Section: Introductionmentioning
confidence: 99%